A phase III randomized trial evaluating the quality of life impact of a tailored versus systematic use of defunctioning ileostomy following total mesorectal excision for rectal cancer—GRECCAR 17 trial protocol. (29th December 2022) - Denost, Quentin; Sylla, Dienabou; Fleming, Christina; Maillou‐Martinaud, Helene; Preaubert‐Hayes, Nathalie; Benard, Antoine; ,
Abstract: Aim: The systematic use of a defunctioning ileostomy for 2–3 months postoperatively to protect low colorectal anastomosis (<7 cm from the anal verge) has been the standard practice after total mesorectal excision (TME). However, stoma‐related complications can occur in 20%–60% of cases, which may lead to prolonged inpatient care, urgent reoperation and long‐term definitive stoma. A negative impact on quality of life (QoL) and increased healthcare expenses are also observed. Conversely, it has been reported that patients without a defunctioning stoma or following early stoma closure (days 8–12 after TME) have a better functional outcome than patients with systematic defunctioning stoma in situ for 2–3 months. Method: The main objective of this trial is to compare the QoL impact of a tailored versus systematic use of a defunctioning stoma after TME for rectal cancer. The primary outcome is QoL at 12 months postoperatively using the European Organization for. Research and Treatment of Cancer QoL questionnaire QLQ‐C30. Among 29 centres of the French GRECCAR network, 200 patients will be recruited over 18 months, with follow‐up at 1, 4, 8 and 12 months postoperatively, in an open‐label, randomized, two‐parallel arm, phase III superiority clinical trial. The experimental arm (arm A) will undergo a tailored use of defunctioning stoma after TME based on a two‐step process: (i) to perform or not a defunctioning stoma according to the personalized risk of anastomotic leak (defunctioning stoma only if modified anastomotic failure observed risk score ≥2) and (ii) if a stoma is fashioned, whether to perform an early stoma closure at days 8–12, according to clinical (fever), biochemical (C‐reactive protein level on days 2 and 4 postoperatively) and radiological postoperative assessment (CT scan with retrograde contrast enema at days 7–8 postoperatively). The control arm (arm B) will undergo systematic use of a defunctioning stoma for 2–3 months after TME for all patients, in keeping with French national and international guidelines. Secondary outcomes will include comprehensive analysis of functional outcomes (including bowel, urinary and sexual function) again up to 12 months postoperatively and a cost analysis. Regular assessments of anastomotic leak rates in both arms (every 50 randomized patients) will be performed and an independent data monitoring committee will recommend trial cessation if this rate is excessive in arm A compared to arm B. Conclusion: The GRECCAR 17 trial is the first randomized trial to assess a tailored, patient‐specific approach to decisions regarding defunctioning stoma use and closure after TME according to personalized risk of anastomotic leak. The results of this trial will describe, for the first time, the QoL and morbidity impact of selective use of a defunctioning ileostomy and the potential health economic effect of such an approach.